Analisis Komparasi Struktur Modal, Total Asset Turnover, Likuiditas, Gross Profit Margin dan Kinerja Keuangan terhadap Perusahaan Besar & Perusahaan Kecil di Perusahaan Industri Konsumsi Bursa Efek Indonesia - Joscelyn Antonius; Yanuar Dananjaya; Victor Soeindra (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine capital structure, total asset turnover, liquidity, gross profit margin, capital structure, total asset turnover, liquidity and gross profit margin on the financial performance of small and large consumption sector companies. The total population is 66 companies, while the sample is 59 companies and the number of observations is 295 reports. The data collection method uses financial reports. The data analysis technique uses multiple linear regression analysis with SPSS version 25. The research results show that capital structure and liquidity have no effect on the financial performance of small and large consumer sector companies. Total Asset Turnover and Gross Profit Margin have a positive effect on the financial performance of small and large consumption sector companies. Keywords: Gross Profit Margin, Liquidity, Capital Structure, Total Asset Turnover